Modellbasierte Entwicklung funktional sicherer Hardware nach ISO 26262 - Adler, Nico (Steinbuch Series on Advances in Information Technology / Karlsruher Institut für Technologie, Institut für Technik der Informationsverarbeitung, 2015)
The compliance with functional safety according to the standard ISO 26262 in context of the increasing electrification of road vehicles is a significant challenge. This work provides a concept and methodology for the model-based development of functional safe hardware. This is characterized by the description of hardware designs, annotation of failure data and performing the demanded safety evaluations.